KILOMETER 500, DIE BEEINDIGING VAN DIE SUIDWES-AFRIKA-KAMPANJE 70 JAAR GELEDE - J.J. Bruwer (Scientia Militaria, 2012)
Examining the final Military actions of July 1915, which led to the historic events of the 9th of July 1915 at Kilometer 500, the turning point of these events may be easily identified. It was namely at the point in time when the German Forces retreated to Khorab, and the Otavi - Otavi Mountains - Elephant Mountain area came into the possession of the Union Forces. This article deals with the chain of events leading to and surrounding the conclusion of the South West Africa Campaign 70 years ago.